The Changing Role of the Educational Video in Higher Distance Education - Laaser, Wolfram; Toloza, Eduardo Adrian (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The article argues that the ongoing usage of audio visual media is falling behind in terms of educational quality compared to prior achievements in the history of distance education. After reviewing some important steps and experiences of audio visual digital media development, we analyse predominant presentation formats on the Web. Special focus is put on recent development of new ways to generate graphics and to create animation sequences, as well as on the video presentation formats used in MOOCs. We conclude that the "new" features are in no way disruptive innovations in distance education and that the potential of video has not been sufficiently exploited. Adequate incentives to use these media for collaborative learning have not been provided and student-generated video content is at present just starting to be considered useful in instructional design.